2021
DOI: 10.1111/jam.15099
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel visual detection methodology for Salmonella in meat using saltatory rolling circle amplification

Abstract: Aim:The aim of this study was to develop a saltatory rolling circle amplification (SRCA) assay for rapid, simple and visual detection of Salmonella in meat. Methods and Results: Saltatory rolling circle amplification assay was established using simple PCR primers targeting the invA gene of Salmonella enterica. The specificity of the SRCA assay was determined using 28 Salmonella and 15 non-Salmonella strains. The analytical sensitivity of the developed SRCA, conventional and real-time PCR assays were 70 fg, 7 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Therefore, more effort is needed to improve the performance of RCA in conjunction with biosensors in detecting pathogens in food samples. Nevertheless, a study reported that RCA technology could detect pathogens in pork better than conventional PCR and qPCR ( Milton et al, 2021b ).…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, more effort is needed to improve the performance of RCA in conjunction with biosensors in detecting pathogens in food samples. Nevertheless, a study reported that RCA technology could detect pathogens in pork better than conventional PCR and qPCR ( Milton et al, 2021b ).…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
“…SRCA follows an initial amplification mechanism similar to RCA, using a circular DNA template and a DNA polymerase with strand displacement activity. However, during the SRCA process, specific recognition sites within the template sequence are encountered ( Milton et al, 2021b , Milton et al, 2021a , Milton et al, 2021c , Zhang et al, 2019a ). At these recognition sites, DNA-cutting enzymes, such as restriction endonucleases or nicking enzymes, introduce breaks in the circular DNA.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, SRCA assays have been exploited in Salmonella, 34 Staphylococcus aureus, 113 Shigella, 112 Cronobacter sp., 114 Clostridium perfringens 115 and Alicyclobacillus acidoterrestris. 100 As a signal amplification technology, RCA can be employed in combination with numerous biosensor technologies to detect pathogenic bacteria. Chen et al combined LAMP with RCA technology and adopted molecular beacons to pair the amplification products to emit fluorescence.…”
Section: Detection Of Pathogenic Bacteriamentioning
confidence: 99%
“…Up to now, SRCA assays have been exploited in Salmonella , 34 Staphylococcus aureus , 113 Shigella , 112 Cronobacter sp., 114 Clostridium perfringens 115 and Alicyclobacillus acidoterrestris . 100…”
Section: Applications Of Biosensors Based On Rca In Biological Detectionmentioning
confidence: 99%